Detecting Epistatic Interactions in Metagenome-Wide Association Studies by metaBOOST - Wu, Mengmeng (Hindawi Publishing Corporation, 2014)
Material and Methods. We recall the definition of epistasis and extend it for metagenomic biomarkers and then we describe the overview of our method metaBOOST and provide detailed information about each step of metaBOOST. Results. We describe the data sources for both simulation studies and real metagenomic datasets. Then, we describe the procedure of simulation studies and provide results for it. After that, we conduct real datasets studies and report the results. Conclusions and Discussion. Finally, we conclude our method and discuss some possible improvements for the future.